Everyday reading in aphasia: Does advance picture context influence reading speed and comprehension?. Issue 11 (2nd November 2021) - Nguyen, Hanh; Morris, Julie; Webster, Janet; Nickels, Lyndsey
ABSTRACT: Background: Both reading speed and comprehension at the text level are often impaired in people with aphasia, potentially impacting their daily life. Provision of advance context (e.g., pictures provided to the reader prior to reading) is found to facilitate text processing and comprehension in typical readers. However, there has been no investigation of whether advance context influences reading in people with aphasia, although some studies have found no benefit on people with aphasia's comprehension accuracy from contextual supports presented simultaneously with text. It also remains unclear whether context may impact people with aphasia's understanding of any particular type of textual information (main ideas vs details, stated ideas vs implied ideas). Aims: This study aimed to investigate the effect of advance picture context on reading speed, overall comprehension accuracy and comprehension of different types of ideas for naturalistic everyday texts in people with aphasia. Methods & Procedures: Twenty-nine adult typical readers and 10 people with aphasia with varying reading ability took part in the study. Participants read three matched sets of short news articles which were either preceded by a related picture, no picture, or (as fillers) an unrelated picture and were followed by multiple-choice comprehension questions. For each text, the questions assessed the understanding of a stated main idea, an implied main idea, a stated detail, and an implied detail. Mixed-effects regression analyses were performed to examine the effect of advance (related) picture context on participants' reading time and comprehension accuracy. Outcomes & Results: The results showed a significant effect of advance picture context on reading speed, with both typical readers and readers with aphasia showing significantly shorter reading times when a picture was available. Advance context did not affect overall comprehension accuracy or accuracy for any subtype of textual information for either group of participants. Conclusion: Advance context facilitates text processing in people with aphasia, resulting in increased reading speed for everyday texts, although it does not influence their comprehension accuracy for these types of texts. This suggests that therapeutic approaches could develop more effective use of advance contextual organisers in order to increase people with aphasia's reading efficiency and ultimately, their confidence and pleasure in reading.